2012
DOI: 10.1002/cne.23010
|View full text |Cite
|
Sign up to set email alerts
|

Failure of lower motor neuron radial outgrowth precedes retrograde degeneration in a feline model of spinal muscular atrophy

Abstract: Feline SMA is a fully penetrant, autosomal recessive lower motor neuron disease in domestic cats that clinically resembles human SMA Type III. A whole genome linkage scan identified a ~140 kilobase deletion that abrogates expression of LIX1, a novel SMA candidate gene of unknown function. To characterize the progression of feline SMA, we assessed pathological changes in muscle and spinal cord from 3 days of age to beyond onset of clinical signs. EMG analysis indicating denervation occurred between 10 and 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Interestingly, recent findings in different SMA animal models have highlighted the contribution of intrinsic skeletal muscle defects, with disruption of the myogenic program associated with a decrease in myofiber size and an increase in immature myofibers [ 36 ]. A study in an SMA feline model provided convincing evidence that motor neuron degeneration begins distal to the cell body and proceeds retrogradely (« dying-back process ») [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent findings in different SMA animal models have highlighted the contribution of intrinsic skeletal muscle defects, with disruption of the myogenic program associated with a decrease in myofiber size and an increase in immature myofibers [ 36 ]. A study in an SMA feline model provided convincing evidence that motor neuron degeneration begins distal to the cell body and proceeds retrogradely (« dying-back process ») [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of Lix1 expression regulation in skeletal muscle cell differentiation remains elusive. It has been suggested that Lix1 plays a role in radial growth of motor axons observed in feline spinal muscular atrophy [ 123 ]. We identified inverse regulation of Csdc2 expression during differentiation and TNF-α treatment relative to control cells.…”
Section: Discussionmentioning
confidence: 99%